PEMBEKALAN TEKNIK UKIR KAYU BAGI PEMUDA DESA SERENAN SEBAGAI UPAYA REGENERASI AHLI KAYU YANG KIAN LANGKA - -, Chici Yuliana Nadi; Rahayu Adi Prabowo; Kuntadi Wasi Darmojo (Abdi Seni, 2025)
The village of Serenan hosts over 200 small-scale household furniture businesses, producing various wooden furniture items such as tables, chairs, cabinets, wall decorations, and more. In the past, the village thrived and was known as a renowned wood carving center. However, its prominence has gradually declined. The current generation of young wood craftsmen in Serenan focuses primarily on simple carving designs, which are easier to produce. This limited approach, combined with increasing competition from larger furniture industries, has hindered their growth. Furthermore, their conventional sales methods contribute to a downward trend in income. Today, Serenan’s young wood craftsmen recognize the importance of adding “value” to their wooden products by incorporating high-aesthetic wood carving elements. However, they face significant challenges due to limited carving skills, while the village’s master carvers are no longer physically able to provide comprehensive training due to their advanced age. Therefore, this Community Empowerment Program (PKM) is designed to provide insights and training in wood carving, covering the entire process from design and carving to finishing. In addition, online marketing training through social media is offered to help them overcome the low sales volume caused by a narrow target market, resulting from conventional sales practices.